2017
DOI: 10.1136/bmjqs-2016-006224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the I-PASS Nursing Handoff Bundle on communication quality and workflow

Abstract: Implementation of the I-PASS Nursing Handoff Bundle was associated with widespread improvements in the verbal handoff process without a negative impact on nursing workflow. Implementation of I-PASS for nurses may therefore have the potential to significantly reduce medical errors and improve patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 38 publications
0
32
0
11
Order By: Relevance
“…Implementation of the same protocol with nurses resulted in a significant increase in the number of nursing handoffs containing acuity assessments; however, no data concerning anticipatory guidance were reported (Starmer et al, 2017). While the effects of such practices on nurses' judgments still remain to be clarified, it is plausible that they could result in greater agreement between nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of the same protocol with nurses resulted in a significant increase in the number of nursing handoffs containing acuity assessments; however, no data concerning anticipatory guidance were reported (Starmer et al, 2017). While the effects of such practices on nurses' judgments still remain to be clarified, it is plausible that they could result in greater agreement between nurses.…”
Section: Discussionmentioning
confidence: 99%
“…This work joins a growing literature that demonstrates the positive effects gained from standardising communication content and delivery methods 3. The IPASS bundle was initially studied in paediatric residents across the USA4 and was adapted by Starmer et al 2 for use by nurses in a paediatric intensive care unit. These researchers found that implementation of this bundle increased the frequency, quality and efficiency of key handoff elements, including fewer interruptions during nursing shift change 2.…”
mentioning
confidence: 86%
“…In this issue of BMJ Quality and Safety , Starmer and colleagues2 describe a framework, IPASS, to bridge this gap. IPASS stands for  I llness severity;  P atient summary,  A ction list;  S ituation awareness and contingency planning; and  S ynthesis by receiver.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of communication tools has been demonstrated for episodic communication, such as handoffs and time-outs, but not for day-today communication. [33][34][35] Because of the need for effective communication, the use of communication tools is an essential part of the evolving model of pediatric critical care delivery. 1 Two studies found that improving the quality of communication may have the biggest impact on quality care ratings.…”
Section: Communication Toolsmentioning
confidence: 99%